(3GdbUI GdbUjQI ai fLO (B/ s - (3fGja YLH MeOi GdYJjHis; (3NjQi OheI (B: s ((3GdbGgQI (B: s (3fGja YLH MeOi GdYJjHi (B: s, 2014)
(3gPI GdOQGSI ddGYeGd GdbUUjI ai efWbI fLO dHjGf NUhUjI gPG Gdaf GdGOHi GdMOjK heG JaQOJ Hg fLO HYO GdKhQI GdGbJUGOjI heG fJL YfgG ef JWhQ hGJNP GdHMK GdefgL GdhUai ai JMdjdg dGKfJi YTQI eLehYg bUUjI dYTQI cJGH hbO cGfJ GddZI YGedG ef YhGed JTcjd GdbUI GdfLOjI ef MjK TGYQjJgG hMhGQ hhUas
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GddZI GdYQHjI hGOGHgGs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCYeGd GdbUUjI s; (3GdbUI GdbUjQI s; (3fLO (B: (3eLehYIs